Step 1
Find the possible zeroes of h(x)
![h(x)-=x^3-5x^2+5x+3](https://img.qammunity.org/2023/formulas/mathematics/college/1eh31t380ebov1iwewppp6n3ertya5ziy3.png)
![\begin{gathered} \text{Possible zeroes=}(\pm1)/(1),\frac{\pm3_{}}{1} \\ u\sin g\text{ factors of the constant 3 and dividing them by the leading coefficient} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o410n2and9gs91zuifuawinht2pua5wbnu.png)
Hence, the first zero will be 3 because
![\begin{gathered} h(3)=3^3-5(3)^2+5(3)+3 \\ h(3)=27-45+15+3=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g8qx8nm10ca2zbetji7xm3a949wth4daw1.png)
Step 2
Use the factor remainder theorem to get the quadratic equation that will give us the other zeroes.
Note; Since the highest power of the polynomial is 3, the polynomial has 3 roots
Therefore the quotient gotten after the division is;
![x^2-2x-1](https://img.qammunity.org/2023/formulas/mathematics/college/9s8q9nd6x9vc8bsqajfi6g6i78q0k6ho8d.png)
Step 3
Factorize the quotient using the quadratic formula to the get the other zeroes.
![x=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/rxvf73usjbbwyik14knxdemoz21vfz2ufc.png)
where from the quotient
![\begin{gathered} a=1 \\ b=-2 \\ c=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zsh48tytgtslybkiftxx5ncr166szlf494.png)
![\begin{gathered} x=\frac{-(-2)\pm\sqrt[]{(-2)^2-4(1)(-1)}}{2(1)} \\ x=\frac{2\pm\sqrt[]{4+4}}{2} \\ x=\frac{2\pm\sqrt[]{8}}{2} \\ x=\frac{2+\sqrt[]{8}}{2}\text{ or }\frac{2-\sqrt[]{8}}{2} \\ x=\frac{2+2\sqrt[]{2}}{2}\text{ or }\frac{2-2\sqrt[]{2}}{2} \\ x=1+\sqrt[]{2}\text{ or 1-}\sqrt[]{2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/93s4c3xpkl5k1ca0ii281gwqqmnyipgzwc.png)
Hence, the zeroes are;
![x=3,\text{ 1+}\sqrt[]{2},\text{ 1-}\sqrt[]{2}](https://img.qammunity.org/2023/formulas/mathematics/college/9esbunwu5hb427sgrvcab82gr06n98n78j.png)